Textual Contraception : Birth Control and Modern American Fiction - Capo, Beth Widmaier, 1973- (Book collections on Project MUSE., 2007)
"Between the 1910s and 1940s, American women fought for and won the right to legal birth control. This battle was fought in the courts, in the media, and in the pages of American literature. Textual Contraception: Birth Control and Modern American Fiction examines the relationship between aesthetic production and political activism in the birth control movement. It concludes that, by dramatically bringing to life the rhetorical issues, fiction played a significant role in shaping public consciousness. Concurrently, the potential for female control inherent in contraception influenced literary technique and reception, supporting new narrative possibilities for female characters beyond marriage and motherhood." "Merging cultural analysis and literary scholarship, this compelling work moves from a consideration of how cultural forces shaped literary production and political activism to a close examination of how fictional representations of contraception influenced the terms of public discourse on marriage, motherhood, economics, and eugenics." "By analyzing popular fiction such as Mother by Kathleen Norris, radical periodicals such as The Masses and Birth Control Review, and literature by authors from Theodore Dreiser to William Faulkner, and Nella Larsen to Mary McCarthy, Beth Widmaier Capo reveals the rich cross-influence of contraceptive and literary history."--Jacket